Explaining son preference in rural India: the independent role of structural versus individual factors - Rohini P. Pande Nan Marie Astone (Popul Res Policy Rev (2007) 26:1-29, 2007)
Much research has been done on demographic manifestations of son preference, particularly girls' excess mortality; however, there is less research that focuses on son preference itself. This paper analyzes the determinants of son preference in rural India. We separate the independent, relative effects of characteristics of individual women and their households, village opportunities for women and village development, and social norms. We look at both socioeconomic and sociocultural variables. Finally, weexamine whether predictors of son preference differ by desired family size. Our data come from the National Family Health Survey (NFHS) India, 1992-1993. We use an ordered logit model, with dummy variables for state of residence. Our analysis shows that women's education, particularly at secondary and higher levels, is consistently and significantly associated with weaker son preference, regardless of desired family size. Once factors measuring social norms, such as marriage customs, caste and religion, areincluded, economic wealth and women's employment at household or village levels are not significant. Media access remains significant, suggesting an influence of ``modernizing'' ideas. Among social factors, caste and religion are associated with son preference but, once state of residence is controlled for, marriage patterns and cultivation patterns are insignificant. The strength and significance for son preference of many determinants differs by desired family size. Our results suggest that policy makers seeking to influence son preference need to identify and target different policy levers to women in different fertility and social contexts, rather than try an approach of one size that fits all